Ionic Liquid Immobilized Palladium Nanoparticle - Graphene Hybrid as Active Catalyst for Heck Reaction - Srivastava, Vivek (Letters in Organic Chemistry, 2015)
We engineered, graphene based Pd -Nano composites (Pd/RGO) and tested them to catalyze the Heck reaction in [bmim] NTf2 solvent system. High yield, easy product isolation, recycling of the catalytic system and ligand free approach are the main outcomes of this proposed protocol. The proposed protocol was further exploited for the successful synthesis of 3-styryl coumarins in good yield.
Keywords: Ionic liquid